Revitalizing Physiology Education: Integrating Notability and Video-Based Learning - James Davis (Journal of Teaching and Learning with Technology)
This article explores an inventive approach to teaching physiology that blends the use of the Notability app on the iPad with video-based learning. The core idea is to offer students a more dynamic and interactive way to comprehend complex physiological concepts during review sessions and outside of class.